Matrix isolation and low temperature solid state FTIR spectroscopic study of α-furil - Lopes, Susy (2006)
α-Furil [C4H3O–C([double bond, length as m-dash]O)–C([double bond, length as m-dash]O)–C4H3O] has been isolated in argon and xenon matrices and studied by FTIR spectroscopy, supported by DFT(B3LYP)/6-311++G(d,p) calculations. The obtained spectra were fully assigned and revealed the presence in the matrices of three different conformers, all of them exhibiting skewed conformations around the intercarbonyl bond with the two C4H3O–C([double bond, length as m-dash]O) fragments nearly planar. The three conformers differ in the orientation of the furan rings relative to the carbonyl groups: the most stable conformer, I (C2 symmetry; O[double bond, length as m-dash]C–C[double bond, length as m-dash]O intercarbonyl dihedral equal to 153.1°), has both furan rings orientated in such a way that one of their β-hydrogen atoms approaches the oxygen atom of the most distant carbonyl group, forming two H–C[double bond, length as m-dash]C–C–C[double bond, length as m-dash]O six-membered rings; the second most stable conformer, II (C1 symmetry; O[double bond, length as m-dash]C–C[double bond, length as m-dash]O intercarbonyl dihedral equal to 126.9°), has one furan ring orientated as in I, while the second furan group is rotated by ca. 180° (resulting in an energetically less favourable H–C[double bond, length as m-dash]C–C[double bond, length as m-dash]O five-membered ring); in the third conformer, III (C2 symmetry; O[double bond, length as m-dash]C–C[double bond, length as m-dash]O dihedral equal to 106.2°), both furan rings assume the latter orientation relative to the dicarbonyl group. The theoretical calculations predicted the two higher energy forms being 5.85 and 6.22 kJ mol−1 higher in energy than the most stable form, respectively, and energy barriers for conformational interconversion higher than 40 kJ mol−1. These barriers are high enough to prevent observation of conformational isomerization for the matrix isolated compound. The three possible conformers of α-furil were also found to be present in CCl4 solution, as well as in a low temperature neat amorphous phase of the compound prepared from fast condensation of its vapour onto a suitable 10 K cooled substrate. On the other hand, in agreement with the available X-ray data [S. C. Biswas, S. Ray and A. Podder, Chem. Phys. Lett., 1987, 134, 541], the IR spectra obtained for the neat low temperature crystalline state reveals that, in this phase, α-furil exists uniquely in its most stable conformational state.